Inserción de actividades físicas.recreativas en el currículo para la formación de conductores profesionales de la escuela del Sindicato de Choferes profesionales de Machala año 2012. - Hurtado Córdova, Pedro Abricio (2013)
The information gathered in this work has made visible the positive effects of recreational physical activity in humans, and how it helps improve quality of life by strengthening not only the physical but psychological and social.